Demographic vistas : television in American culture - Marc, David (University of Pennsylvania Press, 1996)
In Demographic Vistas, David Marc shows how we can take television seriously within the humanist tradition while enjoying it on its own terms. To deal with the barrage of messages from television's chaotic history, Marc adapts tools of theatrical and literary criticism to focus on key personalities and genres in ways that reward serious students and casual viewers alike.This updated edition includes a new foreword by Horace Newcomb and a new introduction by the author that discusses the ways in which the nature of television criticism has changed since the book's original publication in 1984. A new final chapter explores the paradox of the diminishing importance of over-the-air broadcasting during the period of television's greatest expansion, which has been brought about by complex technologies such as cable, videocassette recorders, and online services.